Asymmetric bilateral hip dislocation: A case report - Mehta, Kshitij; Mehta, Pranav; Chhabra, Manika (Indian Journal of Case Reports, 2024)
Bilateral hip dislocation is a rare phenomenon in which one hip dislocates posteriorly and the contralateral hip dislocates anteriorly. We describe a case of a 32-year-old man with bilateral hip dislocation. The patient arrived at our emergency room 30 min after the trauma, was hemodynamically stable, conscious with a Glasgow Coma Scale of 15, and was unable to stand or even sit. Within 40 min of admission, both hips were lowered using closed manipulation. The right hip was reduced using the Allis maneuver while the left hip was reduced using the reverse Bigelow’s maneuver while lying in the lateral decubitus posture. Before the reduction, clinical management and radiological planning are required. The advanced trauma life support protocol must be followed when properly treating associated lesions.